First Nations Cuisines – Wandel und Professionalisierung indigener Ernährungskulturen in British Columbia, Kanada - Schellhaas, Sebastian (transcript, 2020)
A sound and stimulating introduction to the multi-faceted transformation of Indigenous food cultures on Canada's Northwest Coast.